APPLICATION OF THE 4C MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN PHOTOGRAPHIC MATERIALS IN CLASS XI MM 2 SMK NEGERI 1 MOJOANYAR - Ivan Suseno (Jurnal Scientia, 2022)
The purpose of this study was to determine the increase in student learning outcomes of class XI MM 2 SMK Negeri 1 Mojoanyar Mojokerto Regency through the application of the 4 C model on Photography material. This research is a classroom action research with 2 improvement cycles which include planning, implementation, observation and reflection stages. The action given is to apply the 4 C model to the Photography material. The research was conducted from October to November 2018 in class XI MM 2 SMK Negeri 1 Mojoanyar. The results showed that the implementation of the lesson plans increased from 3.08 in the first cycle to 3.50 in the second cycle. The results of student learning tests showed an increase from classical completeness 77.78% in the first cycle to 88.89% in the second cycle. Student activity shows student-centered learning activities in both cycles with the percentage of activeness 91.89% in the first cycle rising to 94.44% in the second cycle.